Strategi Mempertahankan Suara Dalam Pemilihan Umum Anggota DPRD: Studi DPC Partai Gerindra Kota Semarang - Sulistyarini, Dyah Ayu; Latif, Muhamad; Kurniawan, Dwi Wisnu (Fakultas Hukum Universitas Islam Batik Surakarta, 2025)
One One of the functions of political parties is to carry out political recruitment in the process of filling political positions through democratic mechanisms by paying attention to gender equality and justice, especially in the Gerindra Party to sit in the Semarang City Regional People's Representative Council. The purpose of the study was to determine and analyze the Gerindra Party's strategy in maintaining votes in the 2024 Regional People's Representative Council member election in Semarang City. The problem approach method used is sociological juridical. The results of the study are that the strategy to maintain it, with 4 capitals, namely: 1). Economic: member and administrator contributions, donations, assistance from the Semarang City Government, monthly contributions from members of the Regional People's Representative Council; 2) Social: establishing cooperation (community leaders); 3). Cultural: political heritage of parents; open registration; and academic level; 4). Symbolic: education, cadre training. Habitus: provision, workshops, seminars; field, seat allocation opportunities; doxa, real action.